Breaking the cycles of land degradation: a case study from Ban Lak Sip, Lao PDR - International Water Management Institute (International Water Management Institute, 2005)
This issue of Water Policy Briefing is based on research presented in When ?Conservation? Leads to Land Degradation: Lessons from Ban Lak Sip, Laos (IWMI Research Report 91) by Guillaume Lestrelin, Mark Giordano and Bounmy Keohavong. The research was carried out by the Managing Soil Erosion Consortium (MSEC)?a multi-country collaborative effort to better understand land degradation, and potential solutions, in upland areas of Southeast Asia. MSEC is coordinated by IWMI with substantial contributions from France?s Institute of Research for Development (IRD). MSEC?s primary partner in Laos is the Soil Survey and Land Classification Center. Around the world, intensive farming in fragile environments is taking its toll on natural resources. This has led to greater awareness of the need to use agricultural land sustainably?to maximize yields without compromising the health and productivity of the soil. Laos? current rural-development and land-use policies were influenced in part by exactly such an environmental agenda. However, a recent study has shown that land degradation has actually increased in the village of Ban Lak Sip since these policies were put in place. The study used an innovative multi-scale approach to analyze local land degradation in relation to Laos? broader socioeconomic and political environment. This showed that new policies had created an artificial shortage of land?forcing farmers to crop more intensively, and inadvertently causing more degradation. conventional forms of scientific analysis would have identified the change in farming patterns as the cause of degradation. But, importantly, they would not have pinpointed why the change occurred?information which is vital if ways of resolving the problem are to be found. So, because of the analytical approach used, the case of Ban Lak Sip provides a cautionary lesson in the formulation of environmental policy. Policymakers need to carefully consider the impacts that conservation efforts will have on people?s livelihood strategies, if they are to avoid forcing communities to take up practices that increase environmental degradation. To this end, any environmental policy that imposes restrictions, especially on people?s livelihood activities, will need to offer new opportunities too.